Transformasi Pengelolaan Sumber Daya Manusia di Era AI: Peran Literasi Digital dan Budaya Organisasi di Universitas Galuh Ciamis - Luffi Septian (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to analyze the influence of digital literacy and organizational culture on the transformation of human resource (HR) management in the era of artificial intelligence (AI), with a case study at Galuh University in Ciamis. The background of this research is based on the increasingly rapid development of digital technology that requires organizations, including universities, to adapt their HR management systems towards a more adaptive and data-driven model. The study used a quantitative approach with a survey method on 152 respondents consisting of lecturers and educational staff. Data analysis was conducted using the Structural Equation Modeling Partial Least Squares (SEM-PLS) technique to test the relationship between variables. The results show that digital literacy has a positive and significant effect on HR management transformation. Employees with high digital skills are able to utilize technology to increase efficiency, transparency, and work productivity. In addition, organizational culture has also been shown to have a positive influence on the success of digital transformation, where the values ​​of innovation, collaboration, and adaptation are strengthening factors in the application of AI technology in the workplace. Furthermore, organizational culture strengthens the relationship between digital literacy and HR transformation, indicating that digital competence will be more effective when supported by a work culture that is open to change. Overall, the results of this study confirm that the success of human resource management transformation at Galuh University in Ciamis depends on a balance between individual digital capabilities and organizational cultural values ​​that support innovation. The practical implications of this research are the importance of continuous digital literacy training and strengthening an adaptive organizational culture for universities to effectively transform in the era of artificial intelligence.